Intertextuality as a source of discourse emotionalization and language innovations - Levko, Oleksandr; Kramar, Nataliia (Current issues of Ukrainian linguistics: theory and practice, 2022)
The article is focused on the pragmatic potential of intertextuality in news headlines on the Russian-Ukrainian war in Ukrainian religious media, based on the materials of the websites "Religious Information Service of Ukraine", "Catholic Observer", "Religious Truth", "Spiritual Front of Ukraine", published from the end of February to the beginning of May 2022. It has been established that intertext in the headlines enhances the emotionality of the communicative message in order to shape the intended emotional reaction of the audience to Russian aggression. Intertextual units perform the function of polarizing discourse, increasing the effect of the negative image of the aggressor country and its church leaders, on the one hand, and positive representation of the Ukrainian people in its struggle for freedom, on the other hand. Common sources of intertextuality in religious media are the Bible, historical events, figures and phenomena, works of art, mythological creatures, slogans and mythologemes, the relationship with which emotionalizes communication and enhances the persuasive influence on the recipient by stimulating predictable associations with the source text or symbol. In covering Russian aggression, religious media speakers use biblical apocalyptic images and metaphors, allusions to the suffering of Jesus Christ, the stories of Cain and Abel, David and Goliath. Intertextual units that are originally political slogans or ideologemes, such as the "Russian world" and "protection of the Orthodox", are reappropriated in Ukrainian religious media discourse with the purpose of their discrediting. The article also explores the potential of intertextuality in the field of neologization. Some intertextual phenomena from the fields of fiction and history have given rise to linguistic innovations, such as "orcs" and "ruscism", thus revealing a productive way of neologism formation based on intertextual connections with previous texts and cultural phenomena. The article outlines further prospects of the study of emotional reaction of the religious media addressee to intertext-featuring headlines with the involvement of experimental psycholinguistic and corpus methods.
Keywords: intertextuality, speech influence, persuasive discourse, religious media, neologisms, Russian-Ukrainian war.